Jonge Kunst. - Vrienden van Nederloo (s.l. : Bank Brussel Lambert, 1986)
Verhaeghe, Bernard ; Willocx, Andre ; Vansteenlandt, Rita ; Van Gheluwe, Peter ; Vandekerckhove, Hans ; Snauwaert, Jef ; Niels, Eddy ; Moerman, Piet ; Ghekiere, Joris ; Gentils, Frans ; De Geest, Joris ; D'Hanis, Luc ; Devriendt, Robert ; De Clercq, Rosita Amea ; Castelein, Ingrid ; Bouttens, Philippe ; Bossuyt, Werner
Jonge Kunst, Sint-Pieters-Leeuw, Nederloo, 5 september - 28 september 1986
boek